Analysis of Top ten-Cited Articles Published in the Journal of Indian Association of Pediatric Surgeons Over a 10-Year Period - Anjan Kumar Dhua; Divya Jain; Prabudh Goel; Vishesh Jain; Devendra Kumar Yadav; Minu Bajpai (Wolters Kluwer Medknow Publications, 2021)
Aim: The objective was to identify, analyze, and categorize the characteristics (the type of article, country of origin, institution, authorship, topic, and the number of citations) of the articles published in the Journal of Indian Association of Pediatric Surgeons (JIAPS) from 2008 to 2017, with particular focus on the top ten-cited articles. Materials and Methods: The above characteristics of the individual articles were tabulated in the Microsoft Excel® sheet. The number of citations of an article was obtained from three databases (CrosssRef, MEDLINE, and Google Scholar). A final tally was obtained after removing common entries in the databases. Results: The total number of articles published was 613. There were 255 case reports, 209 original articles and review articles, and 149 brief communications. The top five countries of origin of the articles were India, United Kingdom (UK), Turkey, Iran, and Saudi Arabia, with 526, 14, 9, 7, and 6 articles, respectively. The institution, authorship, and topics of the top ten-cited articles were noted. Conclusion: Case reports are the most common type of articles published in JIAPS. Most of the articles originated from India, followed by the UK and middle-east countries. This analysis may provide insights to the editorial board and the members of IAPS about the trend of research and publications among the pediatric surgeons of India.